Direct relationship between protein expression and progeny yield of herpes simplex virus 1 - Nobe, Moeka; Maruzuru, Yuhei; Takeshima, Kosuke; Maeda, Fumio; Kusano, Hideo; Yoshimura, Raiki; Nishiyama, Takara; Park, Hyeongki; Kozaki, Yoshitaka; Iwami, Shingo; Koyanagi, Naoto; Kato, Akihisa; et al. (mBio, 2025)
Earlier single-cell studies of virus-infected cells have revealed high heterogeneity in the state of viral gene expression and progeny virus yield. Notably, these two aspects have been shown independently, and therefore, the direct relationship between progeny virus production and viral gene expression has been unclear. This study, for the first time, demonstrated the direct and quantitative relationship between viral protein expression and progeny virus production by taking into account their heterogeneities and revealed a threshold for the levels of herpes simplex virus 1 protein expression for progeny virus production, thereby suggesting the existence of a rate-limiting step in progeny virus production.